(3JYdjb GdaQGFO Ydi JSgjd GdahGFOs - (3eMeO Hf CHj HcQ Hf YeQ Hf CHj HcQ Hf eMeO, GdeNRhej GdbQTj, HOQ GdOjf GdeYQha HGHf GdOeGejfj , J (B827 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3ecI s)
(3ChdgG (B:s
(3CeG HYO, adG jNai Cf GdcJGH GdeSei HJSgjd GdahGFO hJcejd GdebGUO, JCdja GHf eGdc s
(3BNQgG (B:s
(3hefgG eG jdGRe HYVge CLGR aj CYLHfj VQH RjO chf RjO eQahY GdeMd Ydi GdaGYdjI Ch GdfjGHI hchfg efUhH GdeMd ajfHZj s
(3GdfSNI HgG MhGTs
(3GdfSNI HgGeTgG MhGTj fbdJ ef NW GdYdGeI GHf bGSe GdYHGOj Ydi gGeT fSNJgs
(3fbdgG eGdcgG eUWai Hf aJM Gddg GdMehjs
(3HgG fXGe GdJYbjHIs
(3HChdgG JedcGJ efgG eG gh SfI (B1083(3g```s
(3hJQLeI ddOeGejfj hagQS ddCH`hGH s
Keywords: (3GdfMhs